Characterization of isolates of Staphylococcus aureus for biofilm formation in goats of Aizawl, Mizoram - C M S CHOWPU; A KUMAR; P BEHERA; L RALTE; T K DUTTA; J LALMUANPUIA (Indian Journal of Animal Sciences)
Staphylococcus aureus are the inhabitants of intricate biofilms holding multiple layers of bacteria embedded inside its extracellular matrix. The development of biofilms is a substantial factor that contributes to the failure of treatments. It is recommended to employ a combination of phenotypic and genotypic approaches in the study of biofilm formation in S. aureus. Among the 43 S. aureus isolates obtained from goats, both culturally and genotypically characterized, it was shown that 14 isolates (32.55%) exhibited the presence of the biofilm-producing gene icaD, while none of the isolates tested positive for the presence of icaA. However, out of the total 32 isolates, which accounts for approximately 74.41% of the sample, biofilm formation was seen using the crystal violet tube adherence method. The findings of this study demonstrate a notable prevalence of the ica genes among Staphylococcus aureus isolates derived from goats. Furthermore, it is seen that the presence of these genes does not consistently correlate with the in vitro development of biofilm. The capacity to produce biofilms can result in treatment inefficacy, posing a significant risk to public health and animal welfare, while also causing financial losses for farmers.